Rupees 10,000 Million-A-Year Self Help Scheme - B. L. Jalan (Planning Commission, 1955)
The two grave problems facing India arc the perpetuation of poverty and threat to freedom. The most effective solution to these problems is to increase the national income and to raise the standards of living of the masses. I have, therefore, conceived a scheme which would increase the national income of the country by Rs. 1,000 crores annually in the very first year of its full implementation; and the amount will naturally further increase with successive stages.
The Self-Help Scheme
Planning Commission Library